Isocoumarins: a new class of selective carbonic anhydrase IX and XII inhibitors - Mehmet Onyılmaz; Murat Koca; Alessandro Bonardi; Mustafa Degirmenci; Claudiu T. Supuran (Taylor & Francis Group, 2022)
Isocoumarins, isomeric to comarins which act as effective carbonic anhydrase (CA, EC 4.2.1.1) inhibitors, were investigated for the first time as inhibitors of this enzyme. A series of 3-substituted and 3,4-disubstituted isocoumarins incorporating phenylhydrazone, 1-phenyl-pyrazole and pyrazolo-substituted pyrimidine trione/thioxo-pyrimidine dione moieties were investigated for their interaction with four human (h) CA isoforms, hCA I, II, IX and XII, known to be important drug targets. hCA I and II were not inhibited by these compounds, whereas hCA IX and XII were inhibited in the low micromolar range by the less bulky derivatives. The inhibition constants ranged between 2.7-78.9 µM against hCA IX and of 1.2-66.5 µM against hCA XII. As for the coumarins, we hypothesise that the isocoumarins are hydrolysed by the esterase activity of the enzyme with formation of 2-carboxy-phenylacetic aldehydes which act as CA inhibitors. Isocoumarins represent a new class of CA inhibitors.